Transfer RNA Derived Small RNAs Targeting Defense Responsive Genes Are Induced during Phytophthora capsici Infection in Black Pepper (Piper nigrum L.) - Asha, Srinivasan; Soniya, Eppurath V. (Frontiers in Plant Science, 2016)
Small RNAs derived from transfer RNAs were recently assigned as potential gene regulatory candidates for various stress responses in eukaryotes. In this study, we report on the cloning and identification of tRNA derived small RNAs from black pepper plants in response to the infection of the quick wilt pathogen, Phytophthora capsici.5′tRFs cloned from black pepper were validated as highly expressed during P. capsici infection. A high-throughput systematic analysis of the small RNAome (sRNAome) revealed the predominance of 5′tRFs in the infected leaf and root. The abundance of 5′tRFs in the sRNAome and the defence responsive genes as their potential targets indicated their regulatory role during stress response in black pepper. The 5′AlaCGC tRF mediated cleavage was experimentally mapped at the tRF binding sites on the mRNA targets of Non-expresser of pathogenesis related protein (NPR1), which was down-regulated during pathogen infection. Comparative sRNAome further demonstrated sequence conservation of 5′Ala tRFs across the angiosperm plant groups, and many important genes in the defence response were identified in silico as their potential targets. Our findings uncovered the diversity, differential expression and stress responsive functional role of tRNA-derived small RNAs during Phytophthora infection in black pepper.